Views of General Practitioners on Indoor Environmental Health Risks in the Perinatal Period - Ibanez, Gladys; Zabar, Jehan; Cadwallader, Jean-Sébastien; Rondet, Claire; Lochard, Matthias; Magnier, Anne Marie (Frontiers in Medicine, 2015)
Introduction The aim of this study was to determine the views of general practitioners (GP) on pollution in infant's home. Methods Four semi-structured focus group with 31 general practitioners (GP) were conducted in two french departments in November 2009, February, March and April 2010. The focus group meetings were analysed using a general thematic analysis. Results Perinatal care is a special health issue and a time of privileged sensitisation. The attitude of health risks are well known in the case of "traditionally" toxic substances. In the case of "emerging" environmental exposure, these attitudes depend on the knowledge, beliefs and experience specific to each practitioner. GPs were acquiring a new role in the field of environmental health, whilst at the same time coming to grips with their own strengths and limitations. The implementation of prevention depends on factors which are specific to the practitioner, but also related to the parents and the organisation of the medical practice. Discussion The sensitisation of GPs to environmental medicine, promotion of eco-citizen education, development of research, and the distribution of information, are some of the means which need to be implemented to prevent harmful exposure of the infant.